Developing Example of Narrative Texts in Local Content Theme for Senior High School - Lesly Martha Cecylia Meka; Susan Ira Nova; Tito Gilang Anas Saputra (General English Education, 2023)
Education is one of the basic needs of society and the state in improving the quality of society. Teaching learning material with local content can help student to improve knowledge about local wisdom. But, there are no local content about Palangka Raya contained in teaching learning material used.This research used ADDIE Model as its research method. The data for this research were obtained from expert, English teacher grade X and students’ SMA Negeri 5 Palangka Raya. By using research and development with ADDIE model, the researcher develop a teaching material with local content that concentrate writing skill of the examplary of narrative texts according to the syllabus from the Ministry of Education and Culture of Indonesia. The product from this study are helped the teacher to provide good narrative text with local content of Palangka Raya.The results of this study showed that a good teaching learning material has fulfilled through validation results at an average of 98% by teacher and 97,5% (very valid) by expert. It supported by assessment results at an average 10 by teacher and 10 (A) by expert. Then, the effectiveness based on the results of first trial task at an average 80,56 (Good) and the second trial task get avarage 83,27 (Good). Also, the products received the responses from students in the first meeting with avarge of 84% (Valid) and the second meeting 82% (Valid). From these result, the examplary narrative text can be use and effective to be teaching learning material.